Application of Real-Time PCR Assays for the Diagnosis of Histoplasmosis in Human FFPE Tissues Using Three Molecular Targets (2023)
Histoplasmosis is a fungal infection caused by the thermally dimorphic fungus Histoplasma capsulatum. This infection causes significant morbidity and mortality in people living with HIV/AIDS, especially in countries with limited resources. Currently used diagnostic tests rely on culture and serology but with some limitations. No molecular assays are commercially available and the results from different reports have been variable. We aimed to evaluate quantitative real-time PCR (qPCR) targeting three protein-coding genes of Histoplasma capsulatum (100-kDa, H and M antigens) for detection of this fungus in formalin-fixed paraffin-embedded (FFPE) samples from patients with proven histoplasmosis. The sensitivity of 100-kDa, H and M qPCR assays were 93.9%, 91% and 57%, respectively. The specificity of 100-kDa qPCR was 93% when compared against samples from patients with other mycoses and other infections, and 100% when samples from patients with non-infectious diseases were used as controls. Our findings demonstrate that real-time PCR assays targeting 100-kDa and H antigen showed the most reliable results and can be successfully used for diagnosing this mycosis when testing FFPE samples.